1999
DOI: 10.1007/s002130050814
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1 attenuates scopolamine-induced amnesia in rats and mice

Abstract: Some experimental evidence suggests that the beneficial effects of monosialoganglioside GM1 on learning and memory could be related to an improving effect in central cholinergic function. The present study investigates the effects of GM1 on the memory impairment induced by scopolamine in rats or mice tested in passive (PA) and discriminative avoidance (DA) tasks, respectively. Wistar EPM-1 male rats and Swiss EPM-M1 male mice were treated daily IP with 50 mg/kg GM1 or saline for 7 or 14 days, respectively. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…This kind of inhibitory effect has been reported for scopolamine (Claro et al 1999;Silva et al 1999) and chlordiazepoxide pre-training administration. Alternatively, learning/memory reduction can be evaluated by an increase in the percentage time spent in the aversive enclosed arm (time in the aversive enclosed arm/time in both enclosed arms) in the test, even if the animals were still able to avoid the aversive enclosed arms.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This kind of inhibitory effect has been reported for scopolamine (Claro et al 1999;Silva et al 1999) and chlordiazepoxide pre-training administration. Alternatively, learning/memory reduction can be evaluated by an increase in the percentage time spent in the aversive enclosed arm (time in the aversive enclosed arm/time in both enclosed arms) in the test, even if the animals were still able to avoid the aversive enclosed arms.…”
Section: Discussionmentioning
confidence: 79%
“…The performance of adult rats in DAT was also improved by neonatal GM1 administration . In addition, both GM1 and bovine brain phosphatidylserine (proposed as a treatment of Alzheimer's disease - Crook et al 1992) were able to attenuate scopolamine-induced amnesia in mice tested in this DAT (Claro et al 1999;Silva et al 1999).…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19] The aversive stimuli consisted of a 100 W light and an 80 dB noise. The source of the noise was the horizontal displacement of a piece of metal against wood produced continuously by a small machine placed under the arm.…”
Section: Plus-maze Discriminative Avoidance Taskmentioning
confidence: 99%
“…Our goal was to investigate whether SI-induced depressive-like behaviour would facilitate the retrieval of an aversive (negatively valenced) task: the plus-maze discriminative avoidance task (PM-DAT). [17][18][19] Because our hypothesis presumes that depressive-like behaviour induced by SI would facilitate the retrieval of an aversive task, we first determined a forgetting curve. Then, SI effects were evaluated at a time point at which control mice did not retrieve the task, thereby avoiding a ceiling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenously applied gangliosides are taken up by neurons and integrated into the plasma membrane in the same way as endogenous gangliosides (Morgan & Winick, 1981;Dreyfus et al, 1984) and have been shown to influence the activity of a number of types of neural circuits (Agnati et al, 1983;Silva et al, 1999). Recent studies in rodents demonstrate that gangliosides given intraperitoneally can protect The role and potential of sialic acid B Wang and J Brand-Miller against or reverse age-or lesion-induced memory deficits.…”
Section: Gangliosides and Memory Formationmentioning
confidence: 99%